Synthesis of CeO2/Pd nanocomposites by pulsed laser ablation in liquids for the reduction of 4-nitrophenol to 4-aminophenol. Issue 9 (November 2015) - Ma, Rory; Kim, Yu-jin; Amaranatha Reddy, D.; Kim, Tae Kyu
Abstract: CeO2 /Pd nanocomposites with high catalytic activity were synthesized by pulsed laser ablation in liquids. The size distribution, morphology, crystallinity, and optical properties of these nanostructures were determined by careful characterization using transmission electron microscopy (TEM), X-ray diffraction (XRD), UV−visible spectroscopy, and photoluminescence. The CeO2 /Pd composites consisted of two-dimensional (2D) CeO2 nanoplates with an average size of approximately 20 nm and spherically shaped Pd nanostructures with diameters of 9 nm. The synthesized composite showed a dual-band absorption spectrum with absorption maxima at 266 and 343 nm. The absorption band at 266 nm was assigned to typical inter-band transitions of a metallic Pd system. The other absorption peak, located at 343 nm, was the characteristic band of CeO2 . The photoluminescence spectra showed more significant quenching of the blue emission from the CeO2 /Pd composite compared with that of CeO2 . The CeO2 /Pd composite showed much higher catalytic activity than bare CeO2 nanostructures toward the reduction of 4-nitrophenol to 4-aminophenol. The significant enhancement of the catalytic activity could be ascribed to the interaction between the CeO2 and Pd nanostructures. The unique structure, high catalytic performance, and durability make these materials highly promising candidates for diverse applications in the area of catalysis.